On Lesbian Acts and Female Pleasures in Juvenal Commentaries from Antiquity to 1500 - Schachter, Marc D. (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2015)
This article explores the representation of sex between women in an understudied archive: commentaries on Juvenal’s Satires from antiquity to the end of the fifteenth century. By tracking the changes in glosses to a passage in the Sixth Satire that refers to sex between women, it contributes to our understanding of how and when the discourse on sex between women changed with the rise of humanism and the increased availability of classical texts after the advent of print in Europe. The article also addresses the vexed question of “lesbian” sex and female pleasure as understood in early modernity by considering the interpretations offered for Juvenal’s mention of urinating women and their urine—which was sometimes taken to be female sperm generated through sexual contact between women. The article tracks how the implications of this generation are addressed in different commentaries to either emphasize or downplay female pleasure.